Electrostatically Stabilized Nanofluid Preparation by Chemical Co-Precipitation and the Effect of Particle Size on Nanofluid Viscosity. Issue 3 (3rd July 2018) - Lin, Ting-Wei; Weng, Huei Chu
Abstract: In this study, electrostatically stabilized nanofluids with different particle sizes were prepared by chemical co-precipitation with double-sided titration process, and the effect of particle size on nanofluid viscosity was investigated and analyzed. Conditions of temperature, pH value, and acidic aqueous solution molarity during the experiments were adjusted to obtain electrostatically stabilized Fe3 O4 nanoparticles of different sizes. The viscosity of fluids containing suspended nanoparticles was then measured at different temperatures to determine the effect of particle size. The results showed that an increase in the temperature of the co-precipitation environment caused an increase in particle size. However, an increase in the pH value caused a reduction in particle size. The particle size obtained with lower molarities of acidic aqueous solution was smaller than that obtained with higher molarities. The viscosity of electrostatically stabilized nanofluids with smaller particles was found to be higher than that of fluids with larger particles in fluids with the same concentration of particles. Abstract :